2012
DOI: 10.4028/www.scientific.net/ddf.322.163
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Stainless Steels: A Dozen of Significant Phase Transformations

Abstract: During processing or use, duplex stainless steels are subject to a great number of significant phase transformations, such as solidification, partial ferrite transformation to austenite, ferrite eutectoid decomposition to sigma phase plus austenite, chi phase precipitation, chromium carbide precipitation, chromium nitride precipitation, ferrite spinodal decomposition, phase dissolution during solution annealing, forming of two types (epsilon and alpha prime) of strain induced martensite, martensite reversion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 19 publications
0
14
0
14
Order By: Relevance
“…Addition of alloying elements influences the composition, microstructure and can improve mechanical properties [18]. One limitation of using DSS is the numerous phase transformations occurring in broad temperature range from 300 • C to 1300 • C [19,20]. The intermetallic phases precipitate and induce a negative effect on the toughness and performance of DSS [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Addition of alloying elements influences the composition, microstructure and can improve mechanical properties [18]. One limitation of using DSS is the numerous phase transformations occurring in broad temperature range from 300 • C to 1300 • C [19,20]. The intermetallic phases precipitate and induce a negative effect on the toughness and performance of DSS [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Fast cooling rates during heat treatment can influence the formation of intermetallic sigma phase. Studies carried out [48] and shown by TTT diagrams indicate cooling rates (higher Stainless Steels and Alloys than 250°C/hr) can completely avoid sigma precipitation. The test instrument for the high temperature mechanical testing is Gleeble 3800 .…”
Section: Mechanical Performance and Microstructural Studies Of Slm Stmentioning
confidence: 95%
“…Além disso, nos aços inoxidáveis duplex a ferrita é termodinamicamente metaestável entre 600 e 1000 ºC e possui teores altos de elementos como cromo e molibdênio formadores de fase sigma. Portanto, a precipitação da fase sigma ocorre principalmente pela decomposição da ferrita e resulta no empobrecimento do cromo e do molibdênio em regiões próximas as da formação dessa fase deletéria, reduzindo a resistência a corrosão desses aços [16] [17].…”
Section: Figuraunclassified